Sorghum improvement as biofuel feedstock: juice yield, sugar content and lignocellulosic biomass. - Godoy, Jayfred Gaham Villegas (Kansas State University, 2011)
Sorghum [Sorghum bicolor (L.) Moench] is listed as one of the potential feedstock sources for biofuel production. While sorghum grain can be fermented into ethanol in a similar way as maize, the greatest potential of the crop is based on its massive biomass and sugar rich juices. Thus development of the crop as alternative energy source requires improvement of these traits. The objectives of this study were (1) to determine the mode of inheritance of traits related to ethanol production and identify suitable genetic sources for use in breeding programs, and (2) to evaluate the potential of low lignin mutations for biomass feedstock production and assess biotic stress risks associated with deployment of the mutations. The study consisted of three related experiments: (i) estimating the combining ability of selected sweet and high biomass sorghum genotypes for biofuel traits and resistance to stalk lodging, (ii) determine the impact of brown mid-rib mutations on biofuel production and their reaction to infection by Macrophomina phaseolina and Fusarium thapsinum, and (iii) assess the reaction of low lignin mutants to green bug feeding. In the first experiment six sorghum genotypes of variable characteristics (PI193073, PI257602, PI185672, PI195754, SC382 and SC373) were crossed to three standard seed parent lines ATx3042, ATx623 and ATx399. The resulting hybrids and the parents were evaluated at four locations, three replications during 2009 and 2010 seasons. Data were collected on phenology, plant height, juice yield, °brix score and biomass production. In the second experiment, two brown mid-rib mutations (bmr6 and bmr12) and their normal versions were studied in four forage sorghum backgrounds (Atlas, Early Hegari, Kansas Collier and Rox Orange). The experiment was planted in four replications and at 14 d after flowering five plants in a plot were artificially infected with F. thapsinum and another five with M. phaseolina. The plants were harvested and rated for disease severity (lesion length and nodes crossed). Another five normal plants in each plot were harvested and used to determine biofuel traits (juice yield, ºbrix score and biomass). In the third experiment, a subset of entries evaluated in experiment II and three tolerant and susceptible checks were tested for greenbug feeding damage. Biotype K greenbug colony was inoculated to each genotype using double sticky foam cages. Feeding damage was assessed as percent chlorophyll loss using SPAD meter. There was significant general combining ability (GCA) effect among the male entries for juice yield, stem obrix and biomass production indicating that these traits are controlled by additive genes. Lines PI257602 and PI185672 in particular, had the highest GCA for all the traits and should serve as excellent breeding materials. There was no significant difference among the bmr mutants and between the bmr and normal genotypes for both stalk rot and greenbug damage. In conclusion, juice yield, °brix and biomass are largely controlled by additive genes and hence are amenable to genetic manipulation. The bmr mutations despite their impact on lignin content do not increase risk of attack by stalk rot pathogens and greenbugs and thus can be deployed for biofuel production without incurring losses to these factors.
Keywords: Sorghum bicolor; Combining ability; Biofuel; Stalk rot; Agronomy (0285)